The Effect of Cold Water on Pain Evaluation During Negative Pressure Wound Therapy Dressing Changes: A Prospective, Randomized Controlled Study. (December 2022) - Chattinnakorn, Suphot; Suwajo, Poonpissamai; Meevassana, Jiraroch; Nilprapha, Kasama; Pungrasmi, Pornthep; Promniyom, Pasu; Iamphongsai, Seree; Jindarak, Sirachai; Angspatt, Apichai
Negative pressure wound therapy (NPWT) is a technique using vacuum dressing to promote wound healing in complicated wound. However, for many patients, the application and removal of the NPWT is source of procedural pain. The authors hypothesized that administering cold sterile water into the NPWT sponge would decrease pain during dressing changes. A prospective randomized controlled study was conducted on 27 patients who were undergoing 81 NPWT wound dressing changes (n = 81) at a single institution between October 2016 and September 2017. Each patient had 3 NPWT dressing changes. Cold sterile water (5.74 °C), room temperature sterile water (26.89 °C), and nothing were randomized and administered in the NPWT tubing into the sponge 10 minutes before changing the dressing in each and every procedure. Pain scores were assessed using a 0 to 10 numeric pain scale. Patients administered with cold water reported less pain than those administered with room temperature sterile water during the dressing change (4 vs 5.67; P < .003), and much less pain than those with nothing instilled before dressing change (4 vs 6.59; P < .001). There is no statistically significant difference in pain score between using the room temperature sterile water group and the control group that instilled nothing (5.67 vs 6.59; P = .065). This study has shown that cold water administered through the suction tubing before the dressing change had a better reduction in pain score than using room temperature sterile water and the control group.